Membaca Ulang Kebenaran Di Era Digital Dalam Perspektif Positivisme August Comte - Aji, Wahyu Trisno; Rifqi, Muhammad; Fatoni, Ahmad (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This article aims to explain how positivism is used to obtain knowledge and truth on the internet and social media. This study uses a qualitative method with a narrative-philosophical approach by examining the phenomenon of obtaining information on the internet and social media in August Comte's positivism analysis. This study focuses on a literature review as a source of data. The positivist school emphasizes that truth must be obtained through facts, verification, and confirmation. Auguste Comte describes the journey of human knowledge through three stages: theological, metaphysical, and finally positivistic, where scientific facts become the main basis of understanding. In today's digital age, the flood of information from the internet and social media brings new challenges, as not all information that is disseminated can be trusted. Thus, the positivist approach is important as a tool for sorting out the truth by verifying, analyzing, and confirming information before accepting it as valid knowledge.